Semantic-Pragmatic Evolution of the Latin Prefix SUPER (according to Polish and English) - T. M. Shkapenko; E. V. Shapovalenko (Научный диалог)
The cognitive mechanisms underlying the semantic-pragmatic evolution of the prepositive component of Latin origin super are described. The analysis is carried out on the basis of the data of the modern Polish language, studied in comparison with the data of the English and Latin languages, acting as donors of the semantic-pragmatic evolution of the prefix. It is proved that the locative semantics of the prefix serves as a trigger that starts the processes of metaphorical reinterpretation in modern English. It is shown that the final stage of the pragmatization of the formant is it’s functioning as an evaluative predicate and emotive interjection. It is stated that in the host Slavic language, the specificity of actualization in speech of the super component is determined by the interaction of linguistic and extralinguistic factors. It is emphasized that the integration of post-socialist countries into the global socio-economic space determines the intensive pragmatic-oriented use of this component in advertising discourse and in colloquial speech. It is noted that the influence of the linguistic factor - the features of the word-formation system - determines a new stage in the morphological evolution of the component super. It has been established that, within the affixal derivatives, a new meaning of an element acquiring the status of a root morpheme is being fixed. The relevance of the work performed is determined by the functional and explanative approach to the description of active word-formation processes occurring in modern Slavic languages under the influence of the universal tendency of linguistic globalization.